ANALISIS KINERJA KEUANGAN PADA PT. PRUDENTIAL LIFE ASSURANCE PERIODE 2009-2013 - Ida Zuniarti (Universitas Bina Sarana Informatika, 2015)
Measurement of financial performance of a company is very important, because by knowing its financial performance can be used to assess the success and know the strengths and weaknesses of the company concerned. Information about the financial performance of a company is the information needed by investors, bankers, and creditors that will be used as the basis for making investment decisions and credit. This study aims to determine the financial performance of PT Prudential Life Assurance 2009-2013. The data used are secondary data published financial statements of the balance sheet and income statement obtained by web PT Prudential Life Assurance at www.prudential.co.id. The financial performance of PT Prudential Life Assurance measured using financial ratio is the ratio Return On Equity (ROE), Return On Investment (ROI) and Return on Assets (ROA). Results of studies using financial ratio analysis shows that the financial performance of PT Prudential Life Assurance 2009-2013 period largely decreased. ROA 2009 amounted to 96.49%, in 2010 amounted to 71.62%, in 2011 was 61.20%, in 2012 of 49.10%, and in 2013 amounted to 43.29%. Value ROI 2009 amounted to 9.87%, in 2010 amounted to 9.89%, in 2011 at 12:04%, in 2012 amounted to 8.67%, and in 2013 amounted to 7.71%. ROA 2009 at 9.30%, in 2010 amounted to 9.31%, in 2011 at 8.57%, in 2012 by 6.46%, and by 2013 at 5.11%. Keywords: Financial Performance, ROE, ROI and ROA